«Pregando che ay se debiaset scriver»: society, literacy and graphic mediation in late medieval Bergamo (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The essay studies the results of the rapid increase in the «need to write» that affected the population of Bergamo in the second half of the fifteenth century. A graphical analysis of both commercial obligations and tax declarations of the heads of households is proposed. The effects of the transformations in documentary practices are assessed on three fronts: the composition of the group of the literate; the distribution of graphic skills within the various social and professional contexts; the choices of those who, due to illiteracy or graphic inexperience, accessed document production through the work of professional and non-professional mediators. Differences between urban and rural areas are also reconstructed. In the latter, the lower level of literacy favoured the emergence of serial mediators, sometimes lacking professional writing skills.
Keywords: Palaeography; Bergamo; Renaissance; Writing; Estimi